STRENGTHENING THE MULTICULTURAL CHARACTER BASED ON THE VALUES OF ISLAMIC BOARDING SCHOOLS - Miftahus Salam; Moh. Irmawan Jauhari (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
This study aims to describe and analyze multicultural values ​​in Islamic boarding schools and the kiai's strategy in strengthening multicultural values. The approach in this research is qualitative and the type is phenomenology. The data analysis technique uses the Spradley model where the entire research process consists of: descriptive observation, domain analysis, focused observation, taxonomic analysis, selected observations, component analysis, and ends with theme analysis. The process can be simplified into four stages, namely domain, taxonomy, component, and theme analysis. The results of the study stated that first, the multicultural values ​​that exist in Islamic boarding schools are able to become the foundation of multicultural character because they have long been around and have been applied by residents inside and outside the pesantren. The strategy carried out by the kiai is by exemplary and continuous and systemic habituation. Where exemplary is given by kiai and ustadz, while continuous and systemic habituation is applied in daily life in Islamic boarding schools.